Cost of wild boar to farmers in Sweden. (16th April 2019) - Gren, I -M; Andersson, H; Mensah, J; Pettersson, T
Abstract: Wild boar are widespread mammals in the world that can cause serious economic damage to farmers. Using data from a survey of farmers in Sweden, this study provides estimates of the cost of wild boar (crop loss, machinery damage, protection) to farmers in Sweden. The results indicate that 39 per cent of respondents had experienced at least one of the three types of costs and that they report a wide range of damage values. Regression results from an instrumental variable Tobit model showed that costs are significantly increasing in wild boar abundance and landscape diversity, and decreasing in the share of grain production.